The Legal Significance of Independent Research based on Article 40 DSA for the Management of Systemic Risks in the Digital Services Act - Anna Liesenfeld; Herwig C.H. Hofmann; Felix Pflücke (European Journal of Risk Regulation)
As part of its risk management system, aiming at the mitigation of so-called systemic risks on very large online platforms and very large online search engines (VLOPSEs), the DSA introduces data access rights for independent researchers. With this instrument, the legislator hopes to enable the production of evidence concerning possible threats to society and democracy that might be linked to these platforms or search engines. After an overview of the functioning of the risk management system in the DSA that is characterised by a collaborative governance framework and a learning-based approach, the article will explore the role of the researchers inside this framework. It thereby focuses on the legal significance the researchers’ evidence could have for the risk mitigation obligations imposed on the VLOPSEs in the DSA by interpreting the provisions of the DSA.